Motivation Theories Influencing on Prevention of emerging infectious diseases of Stall Vender in Bangkok and Vicinities (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This study is a descriptive research in the form of correlational research on motivation and the prevention of emerging infectious diseases among street vendors in the Bangkok metropolitan area and its vicinity. A sample group of 420 people was used, and data were collected using questionnaires. The data were analyzed using descriptive statistics, including frequency, percentage, mean, and standard deviation. Based on the health motivation theory, health was categorized into levels, and the variables were grouped. The analysis of factors related to the prevention of emerging infectious diseases was conducted using Chi-square statistics, and the relationship between the prevention of emerging infectious diseases was analyzed using Spearman’s Rho correlation coefficient. The findings indicate that motivation is related to the prevention of emerging infectious diseases among street vendors in the Bangkok metropolitan area and its vicinity.